Accounting Skill Boost: Exclusive Cash Transaction Training for Tangerang City Accounting MGMP Teachers - Kwarto, Febrian; Budyastuti, Triyani (CV. Proaksara Global Transeduka, 2024)
The exclusive training of cash transaction for Subject Teacher Consultation Meeting (MGMP) in Tangerang City aims to improve their competence and understanding in managing cash transactions. This study used direct experimental method to evaluate the effectiveness of the training. Data were collected through discussions and direct interviews to understand participants' perceptions and experiences. The results of this activity showed that the training was successful in significantly improving teachers' competencies. Qualitatively, it revealed that participants felt more confident in teaching cash transactions and were very satisfied with the interactive and relevant teaching methods. In addition, participants reported that this training provided practical skills that can be directly applied in teaching. The conclusion of this training not only improves the competence of individual teachers but also contributes to improving the quality of accounting education in Tangerang City. This study confirms the importance of training that is tailored to the specific needs of participants to achieve optimal results, supporting the findings of previous studies on the positive impact of professional training on education quality.